The role of bacterial carbohydrates in microbe-plant interactions: Rhizobium- legume nitrogen-fixing symbiosis - Carlson, Russell (Henry Stewart Talks, 2012)
Bacterial carbohydrates in microbe-host interactions, Rhizobium cell surface carbohydrates and their role in forming a nitrogen-fixing symbiosis with their host legume, Adaptation of bacterial cell surface carbohydrate structures in response to the host cell, Production of a lipochitin oligosaccharide (LCO) by Rhizobium in response to flavonoids produced by the legume host, Structures and relationship to a host defense response, The plant defense response to rhizobial LCO, The function of Rhizobial LCO as a microbial associated molecular pattern (MAMP), MAMP-triggered immunity, Effector triggered immunity, Rhizobial lipopolysaccharides (LPSs) in symbiosis, Structures of the different LPS structural regions (lipid A, core oligosaccharide, and O-antigen polysaccharide) and their function in symbiosis, The perception of rhizobial LPSs by the host, Is rhizobial LPS a PAMP?, Future research with LPS